Viewing of abstract art follows a gist to survey gaze pattern over time regardless of broad categorical titles - Eugene McSorley; Rachel McCloy; Louis Williams (PLoS ONE, 2025)
Artworks are often shown alongside informative contextual text. This can be as simple as its title and date, or it can be a more descriptive or elaborative explanation of the piece, such as describing its content or explaining the symbolism of the work. Contextual information has been shown to have no impact on early viewing behaviour. A consistent impact on observer eye movement scan paths and fixations is only found in the later periods of looking. One explanation for this is that early eye movement responses to artworks support automatic low-level visual processing that quickly extracts a broad, holistic gist or sense of the works, allowing rapid categorization. The influence of contextual information may only be felt in later periods as it concentrates fixations on descriptive or elaborative elements more quickly and for longer periods. To examine this explanation, we recorded eye movement responses to abstract paintings that were preceded by basic-level categorical labels. In Experiment 1, abstract works were preceded by the labels Landscape, Portrait or Abstract, while in Experiment 2 the labels Action, Still Life or Abstract were given. We found that saccadic eye movements were more common in the first 2 seconds of viewing and were spread over a large portion of the artworks. They became less frequent and were spatially clustered over time. This changing pattern of saccades and their fixation periods was not affected by the contextual information provided by the category labels suggesting a minimal role for top-down control of eye movements when viewers are faced with abstract artworks.